Graphic vandalism: Multi-analytical evaluation of laser and chemical methods for the removal of spray paints. - Giusti, Claudia; Colombini, Maria Perla; Lluveras-Tenorio, Anna; La Nasa, Jacopo; Striova, Jana; Salvadori, Barbara (Journal of Cultural Heritage, 2020)
In this work, we propose the laser-based cleaning with a Q-switched Nd:YAG laser (λ = 532 nm) not as a standalone methodology but rather in combination with chemical agents for the efficient removal vandal signs made with spray paints from marble substrates. The advantage of such approach is based on the preliminary removal of the superficial paint by pulsed laser radiation so as to minimize the risk of the further colorant diffusion in the stone, caused by the solvent-based cleaning that is performed in the second step. The outcome was demonstrated on the removal of five aerosol paints (red, blue, black, green and yellow by Montana Colors 94), whose typology was chosen in agreement with the widespread use of this brand. The influence of substrate characteristics on the cleaning performance, such as roughness, porosity, and ageing of the paint, was investigated on fresh and aged paints on sound marble as well as on fresh paints on aged marble. Fresh and aged paints were characterized in terms of mineralogy and chemistry using X-ray diffraction (XRD), X-ray fluorescence (XRF), Pyrolysis-Gas Chromatography/Mass Spectrometry (Py-GC/MS), Gas/Chromatography/Mass spectrometry (GC/MS). The efficiency for single cleaning step and when applied in sequence was evaluated by colorimetric measurements, optical microscopy on surface and in cross section, XRF and reflection Fourier Transform Infrared spectroscopy (FTIR). Invasiveness of laser cleaning on sound marble was evaluated by Laser Scanner microprofilometry. The results converge in indicating the combined approach as a promising method where the preliminary thinning of the paint layer with laser ablation and the subsequent solvent action proved more efficient than the standalone approaches. The dependence of cleaning efficiency on the paint composition and ageing, as well as on the porosity of the stone, is also discussed.